Enactive approach to communication of normativity in oncoradiology diagnostics - Briedis, Mindaugas; Navarro, Mariano (Medicina e Morale, 2024)
This article examines the enactive approach to oncoradiology imaging and the diagnostic process involved. It investigates how diagnostically relevant knowledge is related to the radiologist's (embodied) subjectivity and (professional) intersubjectivity. Besides identifying a number of correlations between the analysis of embodied cognition and image-based diagnostic praxis, the question of normativity in diagnostic praxis is thematized, which presupposes a social appropriation of biological processes and an urge to achieve optimality in the process of engaging with imaging technology and communication with professionally significant others. The theoretical claims of this research are supported and illustrated by the analysis of actual radiograms.